Los usos del honor por esclavos y esclavas: del cuerpo injuriado al cuerpo liberado (Chile, 1750-1823) - Carolina González Undurraga (Centre de Recherches sur les Mondes Américains, 2012)
This paper tries to explain one of the strategies used by slaves – men or women – and their families when they asked formal justice to be freed or sold : honour. Slaves strategically reinterpreted codes of honor in order to give them cultural legitimacy. We can assume that the body is the privileged place for honor in the slave population, as the violation of their rights, which is interpreted as a violation of their bodies, usually affects the body. Body’s wounds then help to support the accusations against the master for bad treatment, and become one of the principal arguments for selling and for freedom requests.